2022
DOI: 10.1590/s2175-97902022e20422
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Metformin for the prevention and treatment of Tuberculosis

Abstract: The bidirectional relationship between tuberculosis (TB) and diabetes mellitus (DM) is a major concern for medical professionals and epidemiologists as DM affects the severity, progress and outcome of TB and vice versa. Patients affected with TB have a higher rate of morbidity, treatment failure and mortality. Likewise, DM triples the risk of contracting TB and therefore poses a threat to the progress made in the reduction of TB incidence. Hence, it is pivotal to address both the diseases keeping in mind the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…It has also been shown that in the case of tuberculosis, the use of metformin inhibits cell necrosis and contributes to tissue regeneration ( Guler and Brombacher, 2015 ). Metformin also promotes autophagy in infected macrophages and limits the development of mycobacteria by positively influencing the production of reactive oxygen species ( Vyas et al, 2022 ). For this reason, the molecule is currently in clinical trials for the treatment of tuberculosis (NCT05215990, NCT04930744).…”
Section: Potential Candidates For Repositioning In the Treatment Of B...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that in the case of tuberculosis, the use of metformin inhibits cell necrosis and contributes to tissue regeneration ( Guler and Brombacher, 2015 ). Metformin also promotes autophagy in infected macrophages and limits the development of mycobacteria by positively influencing the production of reactive oxygen species ( Vyas et al, 2022 ). For this reason, the molecule is currently in clinical trials for the treatment of tuberculosis (NCT05215990, NCT04930744).…”
Section: Potential Candidates For Repositioning In the Treatment Of B...mentioning
confidence: 99%
“…The antibacterial mechanism of antidiabetic anh hypolipemic drugs is shown in Figure 8 ( Brown, 2015 ; Brindha et al, 2016 ; Guerra-De-Blas et al, 2019 ; Evans and McDowell, 2021 ; Vyas et al, 2022 ).…”
Section: Potential Candidates For Repositioning In the Treatment Of B...mentioning
confidence: 99%